The political pamphlet in the Chilean New Song during the Popular Unity: between love of the process and musical terrorism - Schmiedecke, Natalia Ayo [UNESP] (Univ Do Vale Do Rio Dos Sinos, 2019)
This paper focuses on the pamphlet songs spread by the Chilean New Song movement during the Popular Unity's government (1970-1973), in order to identify the forms assumed by the songs supporting the process, their main characteristics and their repercussion at the time. The analysis was based on the discography of musicians and on the government press, bringing to light the elements involved in the revolutionary discourse supported by the musicians. I found that the repertoire examined is quite varied and was far from a consensus within the movement. The results show that, despite being the most studied and discussed artistic movement in Chilean musical history, there are still many aspects to be explored by scholars, whether in the most well-known field, by reviewing and deepening data, or by bringing up themes, names and works little remembered.
Keywords: Chilean New Song; Popular Unity; pamphlet songs